Knowledge and management of Pediatrician interns on dental caries in children, Paraguay - Díaz-Reissner, Clarisse (2017)
Objective: To determine knowledge and attitude on child dental caries prevention among pediatric interns of XI and XVIII Sanitary Regions (Central and Asuncion Departments) of Paraguay, during 2015. Materials and method: Transversal study. A questionnaire was administered requiring both demographic and academic data, with 10 questions on dental caries knowledge and six question on attitude. Results: Ninety-eight Pediatric interns participated in the study. More than half of participants graduated from private universities (53.06%), they were from Asunción (65.31%), and 68.37% were women. Insufficient knowledge regarding dental caries prevention was found in 83.67%, 16.33% had fair knowledge and none had thorough knowledge. A positive attitude was showed by 96.94%, indifferent attitude was found in 3.16% and none showed a negative attitude about the role on preventing dental caries that pediatricians play. Conclusions: The majority of pediatric interns in question; showed insufficient knowledge yet a positive attitude. Consequently, a more structured oral health prevention curriculum should be enforced during academic instruction as a shared responsibility with pediatricians.